Studi Faktor Risiko Kelainan Miopia Di Rumah Sakit Pertamina Bintang Amin - Titi titi Lestari; Anggunan Anggunan; Tusy Triwahyuni; Rachmat Syuhada (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Vision is a very important sense in determining the quality of human life. In the vision, the eye has a variety of refractive disorders, one of which is myopia. Myopia or nearsightedness is a condition where light entering the eye is focused in front of the retina, making distant objects appear blurred. Many factors cause myopia or nearsightedness, namely age, gender, heredity, and short distance activity. Research Purpose: To determine the risk factors of myopia in Pertamina Bintang Amin Hospital in Lampung Province in 2020. Research Method: This type of research is descriptive quantitative design. The sample in this study were 65 people with a total sampling technique. Data collection using questionnaire sheets and interviews. Data analysis techniques used univariate analysis to determine the frequency distribution of myopia risk factors. Research Result: The results of this study showed that the most common frequency of mild myopia was 39 people (60.0%). The frequency factor of young adult age was 42 respondents (64.6%). The frequency of female gender factors was 37 respondents (56.9%). The frequency of historical factors father/mother's descendants alone were 28 respondents (43.1%). Frequency factors of close-range activity playing computer, cellphone for 1-2 hours as many as 28 people (43.1%), reading books for 1-2 hours as many as 39 people (60.0%), and watching TV for 1-2 hours as much 50 people (76.9%). Conclusion: there is a risk factor of myopia including age, sex, heredity, and close-range activity.